Citizen Science in the Classroom: Data Quality and Student Engagement - Elizabeth Brown; Hung-Ling Liu (The University of Alabama, 2024)
This project sought to evaluate a citizen science project in the classroom via two foci: 1) whether the project could benefit students by increasing their science engagement, and 2) whether students could generate high-quality data. A total of 116 students in two honors biology and four environmental studies classes at a rural high school in the Chesapeake Bay watershed gathered water-quality data from a local stream. Water-quality data gathered from the same area by professionals were obtained from the local water treatment company via email. The quality of the student data was determined by comparing student data to professional data, as well as by eliciting students' understanding of data quality before and after the project via short-answer questions. Students' emotional and behavioral engagement were measured and compared before and after the project using a Likert-type questionnaire, and their behavioral engagement was additionally quantified via observation. The results showed that student data gathered using high-quality instruments were similar to professional data, according to unpaired t-tests. Students' self-reported engagement did not change, but the students' observed behavioral engagement was significantly higher post-intervention. The similarity between student and professional data and the increase in students' behavioral-science engagement show that citizen science has the potential to benefit both students and scientists at the same time, by providing a high-quality dataset while increasing student engagement. This project has implications for formal and informal science education providers, and those interested in developing citizen science programs for youth and adults.